Desempenho de genótipos de soja nos estados de Tocantins, Bahia, Maranhão e Piauí - Mendes, Luiz Ferreira (2011)
This study evaluated the agronomic performance of soybean lines of early to medium and medium late to late cycles in the states of Bahia, Tocantins, Maranhão and Piauí, studying their adaptability and phenotypic stability. The genotypes were evaluated for productivity in the municipalities of Porto Nacional (TO), Balsas (MA) Formosa do Rio Preto (BA), Bom Jesus (PI) and Chapadinha (MA), using a randomized block design with three repetitions. After obtaining the data, analysis of variance and averages were calculated. The methods of stability and adaptability evaluated were: Eberhart and Russell method, and Wricke Annicchiarico method. According to the average yield, it was found that the genotypes UFU 101, UFU 102, UFU 103, UFU 104, UFU 105, UFU 106, UFU 107, UFU 109, UFU 110 and UFU 118, which are from the semi-early to medium cycles, are promising. Regarding the genotypes of medium late to late cycle, UFU 501 line had the best performance in four sites: Formoso do Rio Preto, Chapadinha, Porto Nacional and Balsas. The genotypes UFU 505, UFU 521, Garantia and MSOY 8787 demonstrated superiority in three locations: Chapadinha, Porto Nacional and Balsas. The line UFU 521 was the best one in the three adaptability and stability phenotypic methods studied.